Survival and Pulmonary Injury After Neonatal Sepsis: PD1/PDL1's Contributions to Mouse and Human Immunopathology - Fallon, Eleanor A.; Chung, Chun-Shiang; Heffernan, Daithi S.; Chen, Yaping; De Paepe, Monique E.; Ayala, Alfred (Frontiers in Immunology, 2021)
Morbidity and mortality associated with neonatal sepsis remains a healthcare crisis. PD1−/− neonatal mice endured experimental sepsis, in the form of cecal slurry (CS), and showed improved rates of survival compared to wildtype (WT) counterparts. End-organ injury, particularly of the lung, contributes to the devastation set forth by neonatal sepsis. PDL1−/− neonatal mice, in contrast to PD1−/− neonatal mice did not have a significant improvement in survival after CS. Because of this, we focused subsequent studies on the impact of PD1 gene deficiency on lung injury. Here, we observed that at 24 h post-CS (but not at 4 or 12 h) there was a marked increase in pulmonary edema (PE), neutrophil influx, myeloperoxidase (MPO) levels, and cytokine expression sham (Sh) WT mice. Regarding pulmonary endothelial cell (EC) adhesion molecule expression, we observed that Zona occludens-1 (ZO-1) within the cell shifted from a membranous location to a peri-nuclear location after CS in WT murine cultured ECs at 24hrs, but remained membranous among PD1−/− lungs. To expand the scope of this inquiry, we investigated human neonatal lung tissue. We observed that the lungs of human newborns exposed to intrauterine infection had significantly higher numbers of PD1+ cells compared to specimens who died from non-infectious causes. Together, these data suggest that PD1/PDL1, a pathway typically thought to govern adaptive immune processes in adult animals, can modulate the largely innate neonatal pulmonary immune response to experimental septic insult. The potential future significance of this area of study includes that PD1/PDL1 checkpoint proteins may be viable therapeutic targets in the septic neonate.